Developing a digital climate-linked credit risk scoring tool for micro-finance institutions and livestock owners in Kenya and Guatemala - Vyas, Shalika; Giraldo Mendez, Diana (CGIAR System Organization, 2024)
The Livestock and Climate Initiative focuses on improving climate risk management for livestock producers. Using targeted action research, Initiative scientists are creating ‘investable’ solutions to attract finance for livestock owners exposed to increasing climate variability and hazards, such as drought and heat stress. Under Work Package 2, our implementing partner, the Alliance of Bioversity International and CIAT, worked with microfinance institutions (MFIs) in Kenya and Guatemala to develop innovative, climate-linked credit risk scoring tools that are now facilitating access to credit for dairy farmers and pastoralists. The approach differed slightly, but both countries’ digitally enabled decision support tools have created socially inclusive financial products that embrace climate risk dimensions. This brief describes the different pathways taken to reach our outcomes.